Nietzsche within modernism and the Peruvian avant-garde - Pantigoso Pecero, Manuel (2021)
It begins with a reflection on the similarities of Nietzsches thought to the development of national consciousness and the literary sense der our peoples in its emancipatory stage. Three trends that translate into their aesthetics yes man then analyzed in thematic segments, some features of German philosophical thought in the work of several Peruvian poets are: Vallejo, Guillen Parra del Riego, Hidalgo, Atahualpa Rodríguez, among other.